Cover Feature: Quantum Mechanics/Molecular Mechanics Studies of the Mechanism of Cysteine Proteases Inhibition by Dipeptidyl Nitroalkenes (Chem. Eur. J. 9/2020). Issue 9 (16th December 2019) - Arafet, Kemel; González, Florenci V.; Moliner, Vicent
Abstract : A QM/MM computational study of the inhibition of three cysteine proteases suggests that the dipeptidyl nitroalkene Cbz‐Phe‐Ala‐CH=CH−NO2 must be much more efficient in blocking the activity of the parasitic cysteine proteases than the human ones. Efforts focused on increasing the electrostatic interaction with the residues of the active site and the S2 pocket of these enzymes could be used as a guide to design new potent and selective inhibitors against parasitic cysteine proteases. More information can be found in the Full Paper by K. Arafet, F. V. González, and V. Moliner on page 2002 .